Organized Sport Participation and Physical Activity Levels among Adolescents with Functional Limitations - Ng, Kwok (Sports (Basel), 2017)
Sufficient and regular physical activity is considered a protective factor, reducing the onset of secondary disability conditions in adolescents with chronic diseases and functional limitations. The aim of this study was to explore whether participation in organized sport may be associated to higher levels of physical activity in adolescents with functional limitations, based on a national representative sample. Data from the Health Behaviour in School-aged Children (HBSC) study collected in Finland from two data collection rounds (2002 and 2010) were conducted and pooled from adolescents aged between 13 and 15 years old with functional limitations (n = 1041). Differences in self-reported physical activity over the past week and participation in organized sport activity were analysed for each function. Overall, four in ten (n = 413) participated in organized sport and were significantly (p < 0.001) more physically active (mean = 4.92 days, SD = 1.81) than their non-participating (mean = 3.29, SD = 1.86) peers with functional limitations. Despite low population prevalence, adolescents with epilepsy or visual impairments were the least active if they were not participating in organized sport, yet were the most active if they were involved in organized sport. Participating in organized sport appears to be an important factor promoting resources for maintaining recommended levels of physical activity in Finnish adolescents with functional limitations.